Weapons and the law of armed conflict - Boothby, William H. (Oxford University Press, 2016)
Fully updated to include recent developments in the law of armed conflict, this volume interprets the rules governing the use of weapons, discusses the factors influencing developments in the law, and contextualizes the debate over the direction of weapons law